Law and policy of relevance to the management of plant genetic resources: Learning module with review of regional policy instruments, developments and trends - 2nd edition - Bragdon, S.; Fowler, Cary; França, Z.; Goldberg, E. (2005)
Link to be fixed shortly This module will help professionals who are managing, conserving and using plant genetic resources for food and agriculture in developing countries and/or who have policy-making responsibilities in this field to navigate through the policy environment in such a way as to promote the sound and scientific management of PGR for food and agriculture in their roles as custodians and developers of genetic resources or as policymakrs. It brings together complementary expertise on policy and education concerning plant genetic resources and programme management. The Review of Regional Policy Instruments, Developments and Trends complements the base Learning Module and, as a trainer's tool, it is complete with trends analysis, hand-outs, overheads, case studies, group exercises and selected laws and policies for four regions: Latin America; Sub-Saharan Africa; Central and West Asia and North Africa; and developing countries of Asia, the Pacific and Oceania. The module provides all the guidance needed for people to use the material in training courses. How to use this module provides detailed background to the module, details of its content and organization and guidelines on how make best use of the module. The Overview of the module provides further information about the background and rationale for the module and the approach to learning that underpins its development, while The Learning Plan provides detailed, step by step guidance in the use of the module in training courses. TheCD contains all the material needed to conduct training courses based on the module, including all handouts, incorporating practical group exercises with feedback (as Adobe Acrobat PDF files) and PowerPoint presentations. The module also includes a complete reading list and related laws and policies with Web links. The full text of the module is also included as Microsoft Word files, to allow trainers to extract and customise material as needed for their particular circumstances.